WATER QUALITY PLAYS AN IMPORTANT ROLE IN THE SOCIO-ECONOMIC CONDITION OF THE LOCAL COMMUNITY: A STUDY ON THE KUSHIARA RIVER - Monjur Morshed; Abdullah Al Fatta; Binay Kumar Chakraborty; Tanvir Rahman (International Journal of Ecophysiology, 2024)
In Bangladesh around 7.5% of the fish is harvested from the rivers, being one of the main sources of fish in the country. The water quality of the river must be within standard values to maintain aquatic biodiversity. In this study, water quality, available spaces for fish, and socio-economic status of fishermen were analyzed to find their relationships in Kushiara River, Fenchuganj, Sylhet. Samples of water quality and fish species were collected from August 2017 to September 2021. At the same time, fishermen were surveyed to find out their economic status. The water quality analysis showed all the parameters analyzed (pH, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Dissolved Solid (TDS)) are within the range of international and Bangladesh standards for surface water. The pH, DO, BOD, COD, TDS was respectively 7.1 - 7.99, 5.5 mg/l to 8.4 mg/l, 1 to 4.6 mg/l, 17 to 32 mg/l, 30 to 70 mg/l. Where the local standard is 6.5 - 8.5, more than 5 mg/l, less than 6 mg/l, 17 to 32 mg/l for pH, DO and BOD. The international standard is less than 34.2 mg/l. and 30 to 70 mg/l for COD and TDS in that order. A total of 40 species of fish are recorded in 2017 and 49 in 2021. The average income of a fisherman was 3 USD to 15 USD in the off pick season (December- February), and 7 USD to 30 USD in the peak season (September-November). The fish merchant's daily income was 4 USD to 20 USD in the off-peak season and 7 USD to 30 USD in the peak season. It is concluded that the water quality was adequate for fish diversity and to sustain the socioeconomic condition of the fishermen and fish traders in the Kushiara River.